CGIAR, Vietnam-Cambodia partners, launch CGIAR Asian Mega-Deltas initiative - Bernardo, Eisen (CGIAR System Organization, 2022)
To promote resilient, inclusive, and productive Asian Mega-Deltas, CGIAR, together with government agencies from Vietnam and Cambodia and other relevant stakeholders, officially launched the initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience or AMD through an inception workshop held in TTC Can Tho Hotel, Can Tho City, Vietnam on 28-29 June 2022.